Female Representation in Vocational School Leadership in West Java, Indonesia: A Quantitative Descriptive Study - Rizki Satria Nugraha; Aan Komariah; Taufani Chusnul Kurniatun; Abubakar Abubakar; Sururi Sururi (Jurnal Pendidikan Terapan, 2026)
Purpose: This study aims to describe female representation in vocational school leadership in West Java, Indonesia, particularly in male-dominated vocational fields, and to examine how female and male leaders differ in their perceptions of glass ceiling barriers and stereotype-based pressure. Methods: The study employed a quantitative descriptive design using a cross-sectional survey conducted from 1 to 5 April 2026. Data were collected through a structured questionnaire administered to 120 educational leaders from 40 public and private vocational high schools in West Java. The respondents consisted of headmasters, vice principals, and heads of vocational programs. The data were analyzed using frequencies, percentages, and percentage-point gaps to identify patterns of leadership representation and perceived gender-based barriers. Findings: The findings show that women remain substantially underrepresented in vocational school leadership, with only 23 female leaders or 19.2% of the total respondents, compared with 97 male leaders or 80.8%. Female representation was lowest in mechanics, automotive, industrial machinery, information technology, and construction. Female leaders also reported higher perceptions of glass ceiling barriers and stereotypical pressure than male leaders, indicating that gender inequality is reflected not only in leadership composition but also in organizational experiences. Research Implications: The study implies that vocational schools and education authorities need to strengthen gender-responsive leadership recruitment, promotion, mentoring, and succession systems. Periodic gender audits and professional development programs are also needed to reduce hidden barriers and challenge stereotypes related to technical competence, authority, and leadership suitability. Originality: This study contributes to the literature by providing a descriptive empirical mapping of female leadership representation within gender-associated vocational school environments in Indonesia. Its originality lies in connecting women’s leadership distribution with perceived glass ceiling barriers and stereotype-based pressure in male-dominated vocational fields, an area that remains underexplored in Indonesian vocational education research.